Out of the Streets: Aided Self-Help Housing and Poverty Alleviation through the Townhomes Project of Taguig City - Caballero, Kritzman (Social Sciences and Development Review, 2017)
Poverty is a pervasive problem confronting the developing world. it is so systemic that many types of government interventions have failed in addressing the phenomenon. Measuring poverty does not pertain to pure economics alone but rather it incorporates other dimensions of human reality as part and parcel of this debilitating human condition. it has restricted the potentialities of many individuals to pursue their ends and aspirations. The exponential growth of contemporary cities generates greater costs for people. Poor families from the rural areas migrate and often look for better opportunities in metropolitan areas where most of the resources are available. in the Philippines, most rural dwellers are heavily concentrated in Metro Manila. To lessen this, the government has provided the “Balik Probinsya” or Back to the Province Program, to lessen the overcrowding in cities. The research employed both the qualitative and quantitative method using the descriptive type of research. Using both methods provided the robustness and reliability of the data gathered. The research was intended to find out if a correlation exists between the participation of beneficiaries of the selected community and their self-rated poverty alleviation.